PELATIHAN PENGGUNAAN ROBOT SAR UNTUK MONITORING TEKANAN DARAH ANAK AUTISM - Ramadhani, Dwi; Ekawati Prihatini; Faisal Damsi; Yessi Marniati; Selamat Muslimin; Nyayu Latifah Husni; Husni, M. Daffa Ramadhan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Autism Spectrum Disorder (ASD) is a developmental neurological condition marked by challenges in social communication and repetitive, restrictive behaviors. In Indonesia, there are approximately 2.4 million individuals with ASD, with an additional 500 new cases emerging annually. Anxiety is a prevalent issue among children with ASD, often going unnoticed due to their limited ability to express emotions. To address this, a Socially Assistive Robot (SAR) with a blood pressure sensor can be used to monitor anxiety levels by tracking vital signs, particularly blood pressure, offering an indirect method to detect anxiety. Yayasan Gentaralam SLB Autis in Sumatra Selatan provides crucial support for children with autism, and this project seeks to introduce SAR robots to aid in their care. The robots will serve as non-pharmacological tools to help identify and manage anxiety in children. SAR robots, designed to engage socially, can monitor anxiety by measuring physiological responses, providing a less intrusive yet effective method of assessment. The success of using SAR robots to detect anxiety levels in autistic children depends on various factors, including the child’s autism severity, the setting in which the robot is used, and the child’s emotional condition during the interaction